Lichenicolous fungi of the valley of Ingulets river (Ukraine) (CHORNOMORSKI BOTANICAL JOURNAL, 2015)
The data for lichenicolous fungi of the valley of Ingulets river are given. The list of lichenicolous fungi includes 22 species. Among them, Stigmidium xanthoparmeliarum Hafellner is new for Ukraine. This species forms a gray necrotic spots in thallus and characterized by 4-spore asci and colorless 1-septate spores. Seven species are new to the Dnipropetrovsk region, 2 species are new for Kirovograd region and one species is new to the Mykolayiv region.
Keywords: Stigmidium, lichenicolous fungi, Ingulets.